The attitudes of students of the Faculty of Education at The University of Hama towards E-learning and its relationship to the motivation of academic achievement in the context of the Corona pandemic (Journal of Hama University, 2022)
The Attitudes of Education Faculty students in Hama University towards E-learning and their Relationship with the Motive of Academic Achievement during Corona Epidemic The current study aims at recognizing the attitudes of Education Faculty students in Hama University towards E-learning and their relationship with the motive of Academic Achievement during Corona Epidemic. The researcher used the descriptive analytic approach and applied the scale of the attitude towards e-learning and the scale of the motive of academic achievement on a sample of (313) male/ female students from second and fourth years in Education Faculty in Hama University. The study had the following results: The Attitudes of Education Faculty students in Hama University towards E-learning were positive. - The level of academic achievement was high. There is a statistically significant relationship between the attitudes of students with the motive of academic achievement. There is no statistical difference between the average grades of students in the scale of attitude towards e-learning according to the variable of gender.There is a statistical difference between the average grades of students in the scale of attitude towards e-learning according to the variable of academic year for the sake of fourth year students. There is no statistical difference between the average grades of students in the scale of the motive of academic achievement according to gender variable.There is a statistical difference between the average grades of students in the scale of academic achievement according to the variable of academic year for the sake of fourth year students.The recommendations and suggestions of the study are: Implementing e-learning along with classroom teaching.Encouraging academic research about e-learning especially in graduation projects of undergraduate students. Holding training courses for first year students to teach them how to surf university website and different data learning resources.Designing activities such as a students’ association or electronic activities that enable student to convey their thoughts theoretically and practically. Implementing similar studies in all faculties in Hama University, tackling other variables, and implanting another study to recognize the perspectives of teachers and lecturers towards e-learning. Helping students to be active participants in teaching-learning process, and decision making to enhance their motivation. Helping students to feel that they are valuable members in academic community.